Intraday time‐series momentum: Evidence from China. Issue 4 (5th December 2019) - Jin, Muzhao; Kearney, Fearghal; Li, Youwei; Yang, Yung Chiang
Abstract: This study conducts an investigation of intraday time‐series momentum across four Chinese commodity futures contracts: copper, steel, soybean, and soybean meal. Our results indicate that the first half‐hour return positively predicts the last half‐hour return across all four futures. Furthermore, in metals markets, we find that first trading sessions with high volume or volatility are associated with the strongest intraday time‐series momentum dynamics. Based on this, we propose an intraday momentum informed trading strategy that earns a return in excess of standard always long and buy‐and‐hold benchmarks.